Penerapan Multimedia Pembelajaran Interaktif Berbasis Canva terhadap Minat Belajar Siswa Kelas V SD Negeri Gondoriyo - Mu’affa Fahru Rozaky; Muhammad Abdul Majid; Lintang Ardipratiwi; Yona Rahmawati; Jeihan Salma Aprillia Sari; Ali Ismunadi (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
This research is motivated by the low learning motivation of students in the Natural and Social Sciences (IPAS) subject due to the use of conventional learning methods that are less interesting and the minimal use of interactive media. The purpose of this study is to describe the application of Canva-based interactive multimedia in improving the learning motivation of fifth grade students at SD Negeri Gondoriyo 01. This study uses a qualitative descriptive approach with three main stages, namely planning, implementation, and evaluation. Data collection techniques are carried out through observation, interviews, and questionnaires, while data validity is obtained through source triangulation. The research subjects were 26 students. The results of the study showed that the use of Canva-based interactive multimedia was proven to be feasible and effective in the learning process. This media is able to attract students' attention, increase involvement in learning activities, and generate intrinsic motivation to understand IPAS material more deeply. Therefore, the use of Canva as an interactive learning media is recommended to improve the quality of learning in elementary schools.